PENGARUH UKURAN PERUSAHAAN, AUDIT TENURE, KUALITAS AUDIT, DAN AUDIT REPORT LAG TERHADAP OPINI AUDIT GOING CONCERN - Shulasi Nur Haalisa; Nur Isna Inayati (Review of Applied Accounting Research (RAAR), 2021)
This study aims to analyze the effect of company size, audit tenure, audit quality and audit reportlag on going concern audit opinion. This research is a quantitative research. The data source usedis secondary data in the form of the company's annual financial statements. In this study, goingconcern and audit quality are calculated using a dummy. The population used in this study ismining companies listed on the Indonesia Stock Exchange from 2015 to 2019. Sampling wascarried out by purposive sampling technique method and obtained 29 as 145 observed data. Theresults of this study show that company size, and audit tenure have no effect on going concernaudit opinion. While audit report lag and audit quality heve efeect on going concern opinion